2020
DOI: 10.1002/ijc.32904
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic plasticity potentiates a rapid cyclical shift to and from an aggressive cancer phenotype

Abstract: Highly tumorigenic, drug‐resistant cancer stem‐like cells drive cancer progression. These aggressive cells can arise repeatedly from bulk tumor cells independently of mutational events, suggesting an epigenetic mechanism. To test this possibility, we studied bladder cancer cells as they cyclically shifted to and from a cancer stem‐like phenotype, and we discovered that these two states exhibit distinct DNA methylation and chromatin accessibility. Most differential chromatin accessibility was independent of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…Understanding the relationship between DNA methylation alterations and gene expression changes will provide not only a functional DNA methylation marker for gene expression status, but also a potential therapeutic biomarker, especially for DNA methylation inhibitors [ 88 ]. We recently demonstrated that epigenetic alterations are more frequent than genetic alterations in regulating gene expression, and this may be identified by correlating gene expression with DNA methylation and/or nucleosome accessibility of gene promoters or gene bodies [ 68 , 69 , 83 , 87 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the relationship between DNA methylation alterations and gene expression changes will provide not only a functional DNA methylation marker for gene expression status, but also a potential therapeutic biomarker, especially for DNA methylation inhibitors [ 88 ]. We recently demonstrated that epigenetic alterations are more frequent than genetic alterations in regulating gene expression, and this may be identified by correlating gene expression with DNA methylation and/or nucleosome accessibility of gene promoters or gene bodies [ 68 , 69 , 83 , 87 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in order to better define the prognostic relevance of promoter hypermethylation events in human CRC, this study was designed to characterize epigenetic signatures helpful to identify mCRCs molecular subgroups with defined clinical behavior. In such a context, primary-resistant colorectal carcinomas were selected as cases representative of poor outcome [ 33 ] based on the evidence that methylation modifications are key events used by cancer cells to rapidly adapt to unfavorable environments and acquire drug resistance [ 34 , 35 ]. Our data suggest that the methylation profile of eight functionally methylated genes is predictive of clinical outcome being able to clusterize two independent mCRC cohorts (i.e., the TCGA COAD and the in-house datasets) in two well-defined clusters with hypermethylated tumors characterized by worse prognosis and an MSI-like phenotype compared to hypomethylated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in order to better de ne the prognostic relevance of promoter hypermethylation events in human CRC, this study was designed to characterize epigenetic signatures helpful to identify mCRCs molecular subgroups with de ned clinical behavior. In such a context, primary-resistant colorectal carcinomas were selected as cases representative of poor outcome (33), based on the evidence that methylation modi cations are key events used by cancer cells to rapidly adapt to unfavorable environments and acquire drug resistance (34,35). Our data suggest that the methylation pro le of 12 functionally methylated genes is predictive of clinical outcome being able to clusterize two independent mCRC cohorts (i.e., the TCGA COAD and the inhouse datasets) in two well-de ned clusters with hypermethylated tumors characterized by worse prognosis and a MSI-like phenotype compared to hypomethylated tumors.…”
Section: Discussionmentioning
confidence: 99%